Enhancing Emotional Intelligence to Reduce Stress among Health Sciences Students: A Post-COVID-19 Case Study in Vietnam (Journal of Contemporary Educational Policies and Practices, 2025)
In health sciences education, managing psychological stress is a growing concern that highlights the importance of enhancing emotional intelligence (EI) as a core adaptive competence. This study examines the relationship between EI and perceived stress among Health Sciences undergraduates at Nguyen Tat Thanh University, providing baseline evidence for a future EI intervention program. Using a descriptive cross-sectional design, the data were collected from 100 participants through two validated self-reporting instruments: the Trait Emotional Intelligence Questionnaire–Short Form (TEIQue-SF) and the Perceived Stress Scale (PSS). Descriptive and inferential statistics, including a one-way ANOVA, were processed to compare EI levels across stress categories. The results revealed significant differences in Trait EI among three stress groups - low (M = 4.97, SD = 0.71), moderate (M = 4.34, SD = 0.47), and high (M = 3.59, SD = 0.58) - with an overall effect of F(2, 97) = 27.041, p < .001. Post hoc analysis confirmed an inverse association between EI and perceived stress, indicating that students with higher EI experience lower stress levels. Grounded in Mikolajczak et al.’s (2009) three-level model of emotional competencies, the study proposes a structured EI intervention to strengthen emotional knowledge, abilities, and dispositions that support resilience and well-being in health sciences training. Despite limitations in sample size and institutional scope, the findings offer a robust empirical foundation for future longitudinal and experimental studies evaluating the effectiveness of EI-based interventions in health education.